Pengaruh Nilai Ujian Nasional Matematika terhadap Indeks Prestasi Kumulatif, Mathematics Anxiety dan Self-Regulated Learning - Florianus Martinus Rayoan (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2020)
The purpose of this study is to determine the effect of the national mathematics exam scores on grade point average (GPA), mathematics anxiety, and self-regulated learning of the second-year students of Mathematics Education study program, Faculty of Teacher Training and Education at Nusa Cendana University in a multivariate manner. This study is a correlation research which was conducted at the Faculty of Teacher Training and Education of Nusa Cendana University. The population in this study were the mathematics education program students, Teacher Training and Education Faculty of Nusa Cendana University. The samples consist of 73 students. Data collection techniques used in this research are online questionnaires and documentation methods. Data analysis techniques used in this research are simple linear regression analysis and multivariate analysis of variance (MANOVA) and also hypothesis testing using the t-test and probability level. The result shows that (1) tvalue<ttable = 0,397<1.99394 so that there is no significant influence of the national mathematics exam scores on the students’ GPA, (2) tvalue<t table = -0.270<1.99394 so that there is no significant influence of national examination scores on mathematics anxiety, (3) tvalue<t table = 0,560<1.99394 so that there is no influence between the national math test scores on self-regulated learning, and (4) the MANOVA test shows that the GPA has a significance level of 0.693>0.05, while mathematics anxiety shows a significance level of 0.848>0.05, and self-regulated learning shows a significance level of 0.540>0.05. In conclusion, the national mathematics exam scores in a multivariate manner do not influence the GPA, mathematics anxiety, and self-regulated learning. Keywords: gpa, manova, mathematics anxiety, mathematics national examination scores, self-regulated learning, simple linear regression analysis